Global solvability of a nonlinear Boltzmann equation - Akysh (Akishev), A.Sh. (Bulletin of the Karaganda University. Mathematics Series, 2022)
In this paper, based on the splitting method scheme, the existence and uniqueness theorem on the whole time interval t ∈ [0 ,T ) ,T ≤∞ for the full nonlinear Boltzmann equation in the nonequilibrium case is proved where the intermolecular interactions are hard-sphere molecule and central forces. Considering the existence of a bounded solution in the space C, the strict positivity of the solution to the full nonlinear Boltzmann equation is proved when the initial function is positive. On the basis of this some mathematical justification of the H -theorem of Boltzmann is shown.